Transmission of work attitudes and values: comparisons, consequences, and implications - Kraaykamp, Gerbert; Cemalcilar, Zeynep; Tosun, Jale (The annals of the American Academy of Political and Social Science, 2019)
Are attitudes toward work and perceptions of the benefits of work transmitted from parents to youth similarly across a variety of cultural contexts? What determines the centrality of work to one’s life? How are intrinsic work values (intangible rewards such as autonomy, learning opportunities, and self-fulfillment) and extrinsic work values (such as status, income, and financial safety) shaped; and how do these work attitudes have consequences in the political, economic, and well-being domains? Are the determinants of work values robust across countries, and do the consequences of having certain work values differ by country? These research questions guide this issue of The ANNALS. This introductory article clarifies key concepts underlying the volume and provides an overview of the data sources and analytic approaches addressed in the individual contributions. Most importantly, we provide a broad theoretical framework with notions from various disciplines aimed at giving readers a fuller grasp of the multifaceted significance of work values.
Gesehen am 08.05.2019